Frequency and Extent of Multivessel Coronary Artery Disease in Patients with Non St-Segment Elevation Myocardial Infarction (Nstemi)With Raised Cardiac Troponin-T (CTNT): Extent of Multivessel Coronary Artery Disease in Patients with NSTEMI - Salman, Muhammad; Abbas Khan, Muhammad; Yousaf, Muhammad; ., Inam-U-llah; Hussain, Mumtaz; Sarfraz, Adeel (Pakistan Journal of Health Sciences, 2023)
Myocardial infarction is among the related events in acute coronary syndrome, which also comprise unstable angina pectoris, ST-segment elevation myocardial infarction, and non-ST-segment elevation myocardial infarction. Objective: To determine the prevalence of multi-vessel coronary artery disease in non-ST-segment elevation myocardial infarction with observably increased troponin T concentrations. Methods: There were 284 patients participated in this research. Patients with cardiac troponin T concentrations above 500 ng/l (the recommended limit is 14 ng/l) who had previously had heart problems, tiredness, or other angina-related indications, regardless of gender, between the ages of 30 and 60, were also included in the research. Results: The study group consisted of 95 (33.46%) non-smokers and 189 (66.54%) smokers. Electrocardiogram alterations were detected in 179 (63.02%) participants, whereas no changes were detected in 105 (36.97%) individuals. Additionally, 113 individuals (39.78%) had multi-vessel coronary artery disease, compared to 171 (60.22%) who did not. Conclusion: We come to the conclusion that almost any person with elevated troponin T levels, despite the apparent absence of ST-segment elevation, may undergo cardiac catheterization to ascertain the diagnosis of multi-vessel coronary artery disease.